Pendekatan Formatif dan Sumatif untuk Meningkatkan Mutu Pembelajaran di Sekolah Dasar - Trifina Fitriana; Rusdiana Navlia (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2026)
Educational program evaluation serves as a strategic element to ensure the improvement of learning quality at the elementary school level, particularly as schools are required to be adaptive to students’ diverse learning needs. A major issue frequently encountered is teachers’ limited capacity to implement evaluation models that are simple, sustainable, and relevant as a basis for instructional decision-making. This study aims to analyze the application of simple evaluation through formative and summative approaches as a systematic effort to enhance the quality of learning in elementary schools. The formative approach is employed throughout the instructional process to provide immediate feedback, identify students’ learning difficulties, and adjust teaching strategies in real time, while the summative approach is applied at the end of the instructional period to assess the level of goal attainment and the overall effectiveness of the program. The findings indicate that a balanced implementation of both approaches enables teachers to design learning activities that are more responsive, measurable, and oriented toward continuous improvement. Practically designed simple evaluations also encourage teachers to take an active role as controllers of learning quality rather than merely as curriculum implementers. The conclusion of this study confirms that the integration of formative and summative evaluation in a simple yet systematic manner effectively improves learning quality while strengthening a reflective culture in elementary school settings. The novelty of this study lies in its emphasis on an evaluation model that is easy to apply, contextual, and oriented toward teachers’ daily pedagogical decision-making, thereby offering a practical alternative for elementary schools with limited formal evaluation resources.